IMPLIKASI GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA KARYAWAN - Retno Sari Murtiningsih (Media Riset Bisnis & Manajemen, 2020)
AbstrakPurpose- The purpose of this study was to analyze the influence of transformational and transactional   leadership styles on employees performance. Design/Methodology/Approach- This study uses primary data in the form of questionnaires distributed and filled out by 240 respondents using purposive sampling technique. As the independent variables in this study are transformational leadership style and transactional leadership style, while as a dependent variable is employee performance. To test the hypothesis SEM analysis is used. Finding- The results showed that both transformational leadership style and transactional leadership style had a positive effect on improving employee performance, but the transformational leadership style had a greater influence on employees performance.